Biomechanical analysis of the effect of congruence, depth and radius on the stability ratio of a simplistic 'ball-and-socket' joint model. Issue 10 (October 2016) - Ernstbrunner, L.; Werthel, J-D.; Hatta, T.; Thoreson, A. R.; Resch, H.; An, K-N.; Moroder, P.
Abstract : Objectives: The bony shoulder stability ratio (BSSR) allows for quantification of the bony stabilisers in vivo . We aimed to biomechanically validate the BSSR, determine whether joint incongruence affects the stability ratio (SR) of a shoulder model, and determine the correct parameters (glenoid concavity versus humeral head radius) for calculation of the BSSR in vivo . Methods: Four polyethylene balls (radii: 19.1 mm to 38.1 mm) were used to mould four fitting sockets in four different depths (3.2 mm to 19.1mm). The SR was measured in biomechanical congruent and incongruent experimental series. The experimental SR of a congruent system was compared with the calculated SR based on the BSSR approach. Differences in SR between congruent and incongruent experimental conditions were quantified. Finally, the experimental SR was compared with either calculated SR based on the socket concavity or plastic ball radius. Results: The experimental SR is comparable with the calculated SR (mean difference 10%, sd 8%; relative values). The experimental incongruence study observed almost no differences (2%, sd 2%). The calculated SR on the basis of the socket concavity radius is superior in predicting the experimental SR (mean difference 10%, sd 9%) compared with the calculated SR based on the plastic ball radius (mean difference 42%, sd 55%). Conclusion: The present biomechanical investigation confirmed the validity of the BSSR. Incongruence has no significant effect on the SR of a shoulder model. In the event of an incongruent system, the calculation of the BSSR on the basis of the glenoid concavity radius is recommended. Cite this article: L. Ernstbrunner, J-D. Werthel, T. Hatta, A. R. Thoreson, H. Resch, K-N. An, P. Moroder. Biomechanical analysis of the effect of congruence, depth and radius on the stability ratio of a simplistic 'ball-and-socket' joint model. Bone Joint Res 2016;5:453–460. DOI: 10.1302/2046-3758.510.BJR-2016-0078.R1.